Sensitivity experiments of RegCM4 using different cumulus and land surface schemes over the upper reaches of the Yangtze river - Li, Bingxue; Huang, Ya; Du, Lijuan; Wang, Dequan (Frontiers in Earth Science, 2023)
For the optimal performance of climate simulation, it is critical to localize physical parameterization schemes of climate models, es-pecially in regions with unique geographic characteristics. To study the performance of different physical parameterization schemes for climate simulation in the upper reaches of the Yangtze River Basin (UYRB), we conducted short-term simulations with a resolution of 50 km from 1990 to 1993 using RegCM4 driven by ERA-Interim. Simulations with 72 different scheme combinations were conducted and analyzed to identify the optimal cumulus convection schemes (CSs) and the land surface process schemes in the RegCM4 model. Using the multi-standard scoring method, we evaluated the model performance of precipitation and temperature over the UYRB with different physical parameterization schemes. The results show that precipitation is more sensitive to the CSs than the LSPs. Among the selected CSs, the Kain-Fritsch scheme can better reproduce precipitation characteristics of the UYRB, with a wet bias of only 0.2 mm/day for the multi-year average precipitation. Compared to the community land model (CLM 3.5 and CLM4.5), the Bio-sphere-Atmosphere Transfer Scheme (BATS) performs better in reproducing temperature characteristics of the UYRB, with an average cold bias of only 0.2°C for all BATS schemes. The soil moisture, evapotranspiration and precipitation are lower and sensible heat flux is higher in CLM simulations, which can account for CLMs simulating warmer temperatures than BATS. The results provide a baseline for the localization of the RegCM4's parameterization schemes in the UYRB and other regions of China.